INVESTMENTS IN RENEWABLE ENERGY SOURCES AND CASES OF GOOD PRACTICES OF FISCAL STIMULATION IN THE EU - Mejra Festiđ (Journal of Energy Technology, 2024)
According to the fulfilment of economic criteria of technologies on renewable energy sources and their contribution to the macroͲeconomic environment, there is a need for the establishment of an adequate system of fiscal stimulations. The criteria for such a system of fiscal stimulations of investment in technologies on renewable energy sources is the price of electricity produced by a specific technology with renewable sources. Therefore, we can state the implications for energetic policy: approch of lowering the capital costs, stimulations schemes that are adopted to the lifeͲcycle of the technology and technical efficiency; and acombination of instruments that are related to supply and demand for electricity energy obtained from renewable sources.